Safeguarding financial stability : theory and practice - Schinasi, Garry J.; International Monetary Fund. (Washington, DC : International Monetary Fund, 2006)
The objective of this book is to develop and present a framework for safeguarding financial stability. Part 1 reviews important logical foundations that show how the process of finance is related to real economic processes; part 2 proposes and develops a comprehensive and practical framework for safeguarding financial stability encompassing both the prevention and the resolution of financial imbalances; part 3 examines ongoing real world challenges to financial stability posed by recent structural financial changes such as the globalization of finance etc.
Includes bibliographical references (p. 285-301) and index.
nmn 30/05/13
Loans
Keywords: Finance; Banks and banking, Central; Risk